Assessment of social media from the perspective of digital ethics and human rights - Baydili, Ismail (IGI Global, 2024)
The impact of social media on our lives is significant and extends to a wide audience. However, this impact can sometimes lead to negative consequences. Despite spending a large part of our daily lives on social media platforms, it is observed that a structure to regulate these platforms and protect the fundamental rights of users has not been fully established. Although social media platforms have developed various rules within themselves and made regulations accordingly, the vague nature of these rules can sometimes become a hindrance to establishing order. Consequently, there is a necessity for the establishment of more general and transparent regulations to govern the operations of social media platforms. In this study, the concept of social media, the relationship between social media and privacy, freedom of expression in the context of human rights and communication freedoms are discussed. Subsequently, ethical statements of various social media platforms are examined while maintaining a general perspective. © 2025, IGI Global. All rights reserved.